Penerapan Evidence Based Practice Terapi Kompres Hangat Pada Demam Berdarah Dengue (DBD) dengan Hipertermi - Boseke, Andrew; Mendur, Frida (Yayasan Syalom Cipta Sumikolah, 2025)
Dengue Hemorrhagic Fever (DHF) or Dengue Hemorrhagic Fever (DHF) is a disease caused by the Aedes Eegypty mosquito. This disease is characterized by sudden high fever, without apparent cause, lasting continuously for 2-7 days, accompanied by bleeding manifestations (at least a positive tourniquet test) and/or thrombocytopenia (platelet count ≤ 100,000/μL). This disease is found in almost all parts of the world, especially in tropical and subtropical countries, both endemic and epidemic, with outbreaks related to the arrival of the rainy season. This disease causes many deaths in tropical and subtropical areas and is a health threat to the world because more than 100 countries are infected with this disease. Warm compresses are an evidenced based practice used to reduce hyperthermia because giving warm compresses helps reduce body temperature by means of heat coming out of the skin pores through the evaporation process. A warm compress is an action using a cloth or towel that has been dipped in warm water and applied to certain parts of the body so as to provide a feeling of comfort and reduce body temperature.